BASIN STRUCTURE OF RELIEF IN COLLECTOR GEOSYSTEMS (Scientific journal of the Fergana State University, 2024)
In the article, the basin structure of the relief in the current Amudarya delta collector geosystems is analyzed for the first time. In addition, the tree-like structure of small deltas, which make up the internal structure of the collector basins, is considered. Along with the scientific basis of effective use of Earth's resources of irrigated areas based on the theory of structure, their role in practice is also described.